Perfil hormonal da progesterona em ovelhas (Ovis aries) no início da gestação, no pré-parto e início da lactação - Rodrigues, P. A. (1998)
The main objectives of this work were to determine the physiological patterns of progesterone on pregnancy and lactation in ewes, and to verify whether the hormone presents a 24h secretion rhythm. Serum levels of progesterone increased during gestation with an abrupt decrease by two days preterm. The autocorrelation analysis showed that this hormone, had a more evident circadian rhythm on preterm, than during early pregnancy and lactation.